Personalizing Virtual Reality for the Research and Treatment of Fear-Related Disorders: A Mini Review - Bergsnev, Kamilla; Sánchez Laws, Ana Luisa (Frontiers in Virtual Reality, 2022)
This mini review presents the current state of the art in studies on the personalization of virtual reality for basic research and treatment of fear-related disorders. Of particular interest to the review are the choice of self-report measures and manipulations of contextual factors that researchers are using in their virtual reality procedures. As this mini review will show, work is starting to emerge on the area of the interaction between context and individual differences, yet this topic remains a current gap in the literature on fear learning mechanisms and therapies for fear-related disorders. Studies in this review conclude that virtual reality environments offer many advantages, as they can be adjusted to model different contexts with great precision and control of the experimental context. Virtual reality is also seen by researchers as an opportunity to decrease the translational gap that that exists between the research laboratories and the practical use for therapy treatments in clinics. However, the heterogeneity of methodological approaches that have created replicability as well as comparability issues in the field of fear learning is also a concern in studies using virtual reality. Thus, another, albeit secondary, aim of this mini review will be to point out some of the methodological challenges that should be addressed in future research aimed at the personalization of virtual reality for the research and treatment of fear-related disorders. Factors that will be addressed are a) the use of self-report measures, and b) interactivity aspects of contextual factor design in the virtual reality environment.